ANALISIS KIMIA BATANG AREN (ARENGA PINNATA MERR) YANG BERASAL DARI CIANJUR DAN ANALISIS PENDAHULUAN KAYU AREN YANG BERASAL DARI SUMATERA BARAT - Gusmailina Gusmailina; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
This article describes about Chemical analysis of aren stem (Arenga pinnata Mcrr) from Cianjur and preliminary analysis aren wood from West Sumatera. The analysis comprised of the determination of holocelluloce, lignin, pentosan, tannin, ash content, silica content, and the solubility in cold water, hot water, one percent of sodium hydroxide and alcohol-benzene extractives. The analysis were conducted to determine the chemical component of aren stem from Jasinga, Bogor and chemical component of coconut wood.The average of holocelluloce, lignin, pentosan, tannin, ash and silica, extractives content, solubility in sodium hydroxide of peripheral portion for aren stem from Cianjur were consecutively as follow: 67,79 %, 22,17 %, 19,43 %, 4,07 %, 0,94 %, 0,67 %, 5,62 % (in hot water), 5, 14 % (in cold water), 2,69 % (in alcohol-benzene), 24, 79 % in sodium hydroxide 1 %. While for the central portion, the above analysis showed averages as follow : 48,07 %, 22,95 %, 19,3 %, 16,98 %, 4,41 %, 3,92 %, 17,51 % (in hot water), 12,81 % (in cold water), 7,83 % (in akohol benzene), 31,12 % in sodium hydroxide 1 %.The average of holocelluloce, lignin, pentosan, tannin, ash and silica, extractives content, solubility in sodium hidroxide. of aren wood (peripheral portion) for 63,93 %, 27,08 %, 11,17 %, 5,12 %, 1,50 %, 0,99 %, 1,02 % (in cold water), 2,99 % (in hot water) 4,50 % (in alcohol-benzene), 28,69 % in sodium hydroxide. While for the ruyung enau, the above analysis showed averages as follow : 68,83 %, 22,93 %, 14,0 %, 5,78 %, 1,25 %, 0,92 %, 0,22 % (in cold water), 3,01 % (in hot water), 3,98 % (in alcohol- benzene), 35,57 % in sodium hydroxide.Based on chemical analysis and the comparison to the coconut wood gave a low pentosan and ash content from coconut wood. On the contrary had a high tannin, extractives and silica content to coconut wood.